Development and Evaluation of Instagram Content Based on the 4C Model in Increasing Feraluna Boutique Customer Engagement: Penelitian - Via Yusnika Suhendy; Dedy Husrizal Syah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to develop and evaluate Instagram content based on the 4C model (Context, Communication, Collaboration, Connection) in increasing customer engagement on the Feraluna Boutique Instagram account. The main problem identified is the low engagement rate indicated by the minimal number of interactions on previously published Instagram content. This research uses the Research and Development (R&D) method with the ADDIE model approach (Analysis, Design, Development, Implementation, Evaluation). The data collection process was carried out through observation, documentation, and distributing questionnaires to 94 followers of the @feraluna_boutique Instagram account and expert assessment. The results showed that the application of the 4C model-based content strategy was able to increase impressions by 400.96%, account reach by 518.7%, and interaction by 1900%. Thus, the developed content proved effective in significantly increasing customer engagement. This research provides theoretical contributions to digital marketing literature as well as practical contributions for businesses, especially in the local fashion industry, to optimize the use of social media as an effective promotional tool.